What to pack for the hero's journey: an examination of some concepts relating to heroic figures - Brown, Robert, author; Rollin, Bernard, advisor; Didier, John, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2019)
Heroes are a concept that has existed in almost every culture and period of human history. The contemporary era is no exception, with one example being the incredibly popular and lucrative industry of comic book superheroes. Despite this prevalence however, contemporary philosophy has had little to say about the hero. In this project I try to slightly remedy that situation by examining what the hero may look like in some popular normative ethical theories (nonspecific utilitarianism, Kantianism, and virtue ethics) with the idea that a successful ethical theory should be able to conceptualize the hero. Additionally, I borrow a concept from Ancient Roman culture, the discrimen, to aid in examining heroes ranging from the historic, the everyday, and beyond. Finally, I make some remarks on the inspirational nature of heroes, which I believe to be a significant reason for why philosophers should address the hero. Going forward, I would like to see more robust discussion of heroes in philosophy because of both the positive role they can play as exemplars to aid and facilitate ethical education and ultimately, create a more ethical society.
Keywords: hero; heroic; virtue ethics; heroes; ethics; philosophy